2017
DOI: 10.1177/1535676017735521
|View full text |Cite
|
Sign up to set email alerts
|

Is Your Institution Disposing of Culture Media Containing Antibiotics?

Abstract: The disposal of culture media containing antibiotics is a daily practice in research laboratories at any level (ie, academia, industry, federal/state). Generally, good microbiological practices recommend that the biohazard be treated before disposal of the culture media. This brief summary aims to provide a different angle in the waste management of culture media containing antibiotics from the perspective of handling the biohazard (microbiological agent) and the chemical hazard (antibiotic) before disposal. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Recent reviews have identified the significant and overlooked contribution of inappropriately disposed of antimicrobials as drivers of AMR in both human and veterinary medicine [83]. Whilst there is some guidance around disposal of laboratory waste that contains antimicrobials, there are no equivalent publicly available recommendations for laboratory animal waste containing antimicrobials [84]. Antimicrobials, most commonly reported in the survey, have long-standing environmental impacts.…”
Section: Reported Use May Represent a Risk To Human And Rodent Healthmentioning
confidence: 99%
“…Recent reviews have identified the significant and overlooked contribution of inappropriately disposed of antimicrobials as drivers of AMR in both human and veterinary medicine [83]. Whilst there is some guidance around disposal of laboratory waste that contains antimicrobials, there are no equivalent publicly available recommendations for laboratory animal waste containing antimicrobials [84]. Antimicrobials, most commonly reported in the survey, have long-standing environmental impacts.…”
Section: Reported Use May Represent a Risk To Human And Rodent Healthmentioning
confidence: 99%
“…21 Due to short shelf-life, tons of culture media expire before use and are often discarded. 22 Thus, it is imperative that expired culture media products find other important use as precursors for synthesizing nanomaterials such as CDs or close derivatives. This could reduce the wastage of resources and bring about the large-scale production of carbon-based nanoparticles.…”
Section: Introductionmentioning
confidence: 99%